Geology and flood hazard assessment using geographic information system (GIS) in Dabong, Kelantan - Nur Fatin Firdaus Muhamad Faisal (2023)
Dabong is part of the Gua Musang Group formation, Taku Schist and granite Stong Complex in the western part, which is made up of rocks from the Permian to the Triassic. Extreme flooding has struck Kelantan on multiple occasions, wreaking havoc and costing millions in property damage. It is generally accepted that the heavy monsoon rains are the root cause of those floods. This study has chosen Kampung Dabong, Kelantan to study about flood hazard. The coordinate of the study area is in between 5°24'34.77"N to 5°22'3.60"N latitude and 101°58'34.87"E to 101°58'36.74"E longitude and it covers a region of 25km2. The objective of this study is to update the geological map of Kampung Dabong with scale of 1:25,000, to determine the parameters of the flood hazard and to produce a flood hazard map of the study area. From the result of petrography analysis, this study area consists of metamorphic rock which is schist and phyllite. There are seven parameters of thematic maps for flood hazard map have been identified such as slope map, elevation map, drainage density map, land use map, rainfall map, river density map and flow length map. Weighted Overlay Method (WOM) being applied in ModelBuilder using ArcGIS software to overlay all parameters in order to create flood hazard maps from year 2017 to 2020. The result of flood hazard maps was classified into three classes which is low, moderate and high. From 2017 to 2020, it can be concluded that 81% of the study area falls within the high hazard zone, 10% falls within the moderate hazard zone, and 8% falls within the low hazard zone. In conclusion, the geological map of this study area has been updated and a final flood hazard map has been produced.